2018
DOI: 10.1186/s40164-018-0124-7
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and clinical characteristics of myeloproliferative neoplasms in Malaysia

Abstract: BackgroundThe evolution of molecular studies in myeloproliferative neoplasms (MPN) has enlightened us the understanding of this complex disease consisting of polycythaemia vera (PV), essential thrombocythemia (ET) and primary myelofibrosis (PMF). The epidemiology is well described in the western world but not in Asian countries like Malaysia.Materials and methodsThis retrospective national registry of MPN was conducted from year 2009 to 2015 in Malaysia.ResultsA total of 1010 patients were registered over a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…It is postulated that MPN clonal cells induce the release of inflammatory cytokines, which results in procoagulant states. This finding is supported by blood-clotting markers, i.e., thrombin antithrombin complex, thrombomodulin, von Willebrand factor/factor V111, and prothrombin fragment 1 + 2 [ 45 ]. The majority of our MPN patients had thrombotic events that were commonly due to arterial thrombosis compared to venous thrombosis; this is consistent with most studies [ 42 ].…”
Section: Discussionmentioning
confidence: 85%
“…It is postulated that MPN clonal cells induce the release of inflammatory cytokines, which results in procoagulant states. This finding is supported by blood-clotting markers, i.e., thrombin antithrombin complex, thrombomodulin, von Willebrand factor/factor V111, and prothrombin fragment 1 + 2 [ 45 ]. The majority of our MPN patients had thrombotic events that were commonly due to arterial thrombosis compared to venous thrombosis; this is consistent with most studies [ 42 ].…”
Section: Discussionmentioning
confidence: 85%
“…5,6 Palpable splenomegaly as in the index case, has also been reported in 1/3 of PV patients in Malaysia. 7 Whiles Hb > 16 and 16.5 in women and men respectively should raise suspicion for PV diagnosis, the presence of splenomegaly can mask high Hb and delay diagnosis. Even though this did not occur in our case, clinicians must be mindful of this fact when interpreting Hb results as part of the evaluation for PV.…”
Section: Discussionmentioning
confidence: 99%
“…There is a similar nding to the previous paper of epidemiology of this MPN cohort in which Chinese seems to have a relatively higher incidence of death in MPN compared to Malay considering the racial distribution of 21.2% for Chinese and 61.8% for Malay in Malaysia. [41] Despite the statistical insigni cance, geography and ethnicity are found to in uence the survival in other countries [13]. Maynadie et al revealed that the survival rates of 74% in Northern Europe in comparison to only 27% survival rates in Eastern Europe [21].…”
Section: Discussionmentioning
confidence: 99%